Changes in Mathematics Core Curriculum and Matriculation Exam in the Light of the COVID-19-Shock - Csaba Csapodi; Miklós Hoffmann (MDPI AG, 2021)
The new National Core Curriculum came into force in September 2020 in Hungarian schools. The COVID-19 pandemic has had a deep impact on the final stages of its development. In this paper we have selected two areas for analysis: the fundamental principles of mathematics curriculum and the matriculation exam in mathematics. We propose improvements in both fields, further emphasizing the importance of skills in displaying, understanding and processing information, including visual information obtained as a source or outcome of a problem. We argue that representation, interpretation, and critical evaluation of data and information must be essential parts of the mathematics curriculum. In this context, we also propose a new type of task for the matriculation exam: a complex essay task. The ultimate goal is the development of cross-cutting competencies to support students to become citizens who can make responsible decisions based on the data and knowledge available.